Contribution of corner reflections from oriented ice crystals to backscattering and depolarization characteristics for off-zenith lidar profiling. (June 2018) - Borovoi, Anatoli G.; Konoshonkin, Alexander V.; Kustova, Natalia V.; Veselovskii, Igor A.
Hightlights: Depolarization and color ratios for horizontally oriented ice crystals were calculated. Depolarization peak at 30° lidar tilt for oriented plates was predicted. Corner reflection effect was recently observed by tilted lidar. Abstract: Backscattering Mueller matrix and the depolarization and color ratios for quasi-horizontally oriented hexagonal ice plates have been calculated within the framework of the physical optics approximation. In the case of a tilted lidar, the dependence of the color and depolarization ratios on polarization of the incident light has been analyzed. It is shown that the corner reflection effect inherent to the pristine hexagonal ice crystals results in sharp peaks of both the backscattering cross section and depolarization ratio at the lidar tilts of about 30° off zenith. The experimental results obtained recently by Veselovskii et al.[13] at the lidar tilt of 43° have been interpreted as a partial manifestation of the corner reflection effect. The retrieval of the vertical profile of the ice crystal fraction consisting of quasi-horizontally oriented hexagonal plates has been demonstrated.